Effect of single Vs double insemination on farrowing rate and litter size in sow - KADIRVEL, G; DAS, ANUBRATA; NASKAR, S; HASIN, DILRUBA; BUJARBARUAH, K M (The Indian Journal of Animal Reproduction, 2023)
Semen was collected from Hampshire boar by gloved-hand technique twice weekly and extended in Beltsville ThawingSolution (BTS) at the rate of I :4 to I: 5 depending upon concentration. Seventy to eighty ml of extended semen (2-3 billion sperm)was packed in the sachet and preserved at l 7°C. In group I (No = 25), sows were given single insemination, while Group II (No = 27)received double insemination during standing estrus at 24 h interval. Sows in group III (No =20) were allowed for natural service (NS)and served as control. The farrowing rate with single insemination was 68% with an average litter size of 7.6±0.3. Whereas in doubleinsemination group, the farrowing rate was 77% with an average litter size of 9.2±0.2. There was significant (P~0.05) differencebetween single and double insemination groups on the farrowing rate and litter size. Similarly, the farrowing rate (80%) and litter size(9.4±0.2) in NS group were significantly (P~0.05) higher than that in single insemination group. However, there was no significantdifference between double insemination group and NS group on farrowing rate and litter size . It was concluded that inseminatingestrus sows twice at 24h interval would favour the farrowing rate and litter size, which is more or less equal to single natural mating.
Keywords: Single Vs double insemination; farrowing rate; litter size; sow